Are signals of aggressive intent less honest in urban habitats?. (29th October 2019) - Akçay, Çağlar; Beck, Michelle L; Sewall, Kendra B
Abstract: How anthropogenic change affects animal social behavior, including communication is an important question. Urban noise often drives shifts in acoustic properties of signals but the consequences of noise for the honesty of signals—that is, how well they predict signaler behavior—is unclear. Here we examine whether honesty of aggressive signaling is compromised in male urban song sparrows ( Melospiza melodia ). Song sparrows have two honest close-range signals: the low amplitude soft songs (an acoustic signal) and wing waves (a visual signal), but whether the honesty of these signals is affected by urbanization has not been examined. If soft songs are less effective in urban noise, we predict that they should predict attacks less reliably in urban habitats compared to rural habitats. We confirmed earlier findings that urban birds were more aggressive than rural birds and found that acoustic noise was higher in urban habitats. Urban birds still sang more soft songs than rural birds. High rates of soft songs and low rates of loud songs predicted attacks in both habitats. Thus, while urbanization has a significant effect on aggressive behaviors, it might have a limited effect on the overall honesty of aggressive signals in song sparrows. We also found evidence for a multimodal shift: urban birds tended to give proportionally more wing waves than soft songs than rural birds, although whether that shift is due to noise-dependent plasticity is unclear. These findings encourage further experimental study of the specific variables that are responsible for behavioral change due to urbanization. Soft song, the low amplitude songs given in close range interactions, is an honest threat signal in urban song sparrows. Given its low amplitude, soft songs may be a less effective signal in noisy urban habitats. However, we found that soft song remained an honest signal predicting attack in urban habitats. We also found that birds may use more visual signals (rapid fluttering of wings) in urban habitats to avoid masking from acoustic noise.